Techniques And Parameters Investigations On Crosslinked Rubber Foam Formations. - Sipaut, C. S.; Ariff, Z. M.; Sims, G. L. A.; Nadia, S.; Mohamad Ibrahim, M. N. (2005)

(untitled)
Single Stage. Heat Tranfer and Heat and Chill techniques were applied to determine suitable methods for crosslinked rubber foam formation. Various parameters such as expansion temperature and blowing agent concentration were also investigated.